Development, Optimization, and Validation of a High Throughput Screening Assay for Identification of Tat and Type II Secretion Inhibitors of Pseudomonas aeruginosa - Massai, Francesco; Saleeb, Michael; Doruk, Tugrul; Elofsson, Mikael; Forsberg, Åke (Frontiers in Cellular and Infection Microbiology, 2019)
Antibiotics are becoming less effective in treatment of infections caused by multidrug-resistant Pseudomonas aeruginosa. Antimicrobial therapies based on the inhibition of specific virulence-related traits, as opposed to growth inhibitors, constitute an innovative and appealing approach to tackle the threat of P. aeruginosa infections. The twin-arginine translocation (Tat) pathway plays an important role in the pathogenesis of P. aeruginosa, and constitutes a promising target for the development of anti-pseudomonal drugs. In this study we developed and optimized a whole-cell, one-well assay, based on native phospholipase C activity, to identify compounds active against the Tat system. Statistical robustness, sensitivity and consequently suitability for high-throughput screening (HTS) were confirmed by a dry run/pre-screening test scoring a Z’ of 0.82 and a signal-to-noise ratio of 49. Using this assay, we evaluated ca. 40,000 molecules and identified 59 initial hits as possible Tat inhibitors. Since phospholipase C is exported into the periplasm by Tat, and subsequently translocated across the outer membrane by the type II secretion system (T2SS), our assay could also identify T2SS inhibitors. To validate our hits and discriminate between compounds that inhibited either Tat or T2SS, two separate counter assays were developed and optimized. Finally, three Tat inhibitors and one T2SS inhibitor were confirmed by means of dose-response analysis and additional counter and confirming assays. Although none of the identified inhibitors was suitable as a lead compound for drug development, this study validates our assay as a simple, efficient and HTS compatible method for the identification of Tat and T2SS inhibitors.